The Effect of Mycophenolate Mofetil as First-Line Therapy on the Timing of Urine Protein–to–Creatinine Ratio Reduction in Immunosuppressant-Naive Patients With Lupus Nephritis at a Single Center. Issue 1 (January 2022) - Timlin, Homa; Hardenbergh, Dylan; Fine, Derek; Monroy-Trujillo, Jose Manuel; Haque, Uzma; Adler, Brittany; Vaidya, Dhananjay; Geetha, Duvuru
Abstract : Background/Objectives: Early response to immunosuppressive therapy predicts good renal outcome in lupus nephritis (LN). The purpose of this study was to assess the effect of mycophenolate mofetil (MMF) on the timing of urine protein–to–creatinine ratio reaching 200 mg or less after starting MMF as initial therapy for class III, IV, or V in immunosuppressant-naive patients with LN. Methods: Patients who had a diagnosis of biopsy-proven LN were included in this cohort study. The initial dose of MMF was 1000 mg twice daily. If no improvement, it was increased to 1500 mg twice daily after 1 month. For statistical analysis, exact binomial distribution 95% confidence intervals were calculated. Results: Nine patients were identified. There were 3 patients with class III, 3 with class IV, 1 with class III to V, 1 with class II to V, and 1 with class V lupus nephritis. The majority were African Americans (70%). At baseline, proteinuria ranged between 0.41 and 4 g, and 88% had normal estimated glomerular filtration rate. Forty-four percent of patients reached 0.28 g of proteinuria within 8 weeks of starting MMF (95% confidence interval, 14%–79%), all of which maintained the same level of response and normal estimated glomerular filtration rate at 12 months. Thirty-three percent of patients achieved the American College of Rheumatology complete response at 8 weeks. Conclusions: This study demonstrates that only a minority of immunosuppressant-naive LN patients achieved the American College of Rheumatology complete response at 8 weeks after initiation of MMF. A rapid decline in the proteinuria to 0.28 g within the first 8 weeks of the treatment correlated strongly with achieving the same level of response at 12 months.